Yavi-Chicha and the Inka expansion: A petrographic approach - Cremonte, Maria Beatriz (2014)
The social complexities underlying imperial control are manifest in the material culture of everyday life encountered at archaeological sites. The Yavi-Chicha pottery style of the south-central Andes illustrates how local identities continued to be expressed in practices of pottery manufacture during the process of Inka expansion. The Yavi-Chicha style itself masks a number of distinct production processes that can be traced through petrographic analysis and that relate to the different communities by whom it was produced and consumed. The dispersion of pottery fabric types in this region may partly be attributable to the Inka practice of mitmaqkuna, the displacement and relocation of entire subject populations.